A DECISION SUPPORT SYSTEM IN ELECTION BEST ONLINE BAG DISTRIBUTOR USING SAW METHOD - Feriadi; Zulfahmi Syahputra; Nova Mayasari (INFOKUM, 2022)
The need for bags is in great demand by users. A bag is something that can carry personal items. For women, the bag is one of the symbols of socialite that can increase the status of the people. In this day and age, bags can be purchased online thereby increasing resellers to sell these bags to consumers. Resellers need a good online bag distributor so that customers are not disappointed with the quality of the bag. There are many criteria that can be tested. The SAW method can help determine an online bag distributor that has good quality. Applying this method to resellers will increase the reseller's selling value to customers. The main benefit obtained is that customers can continue to subscribe to these resellers because they have good quality